1967
DOI: 10.1152/ajplegacy.1967.213.2.432
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of endogenous and exogenous gastrin in stimulation of acid and pepsin secretion

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

1968
1968
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…3) could be caused by vagal release of gastrin from portions of the stomach or duodenum (14) not included in the antral The findings of the present study confirm an earlier study from this laboratory (13) that the maximal response of HPs to exogenous gastrin was higher than to endogenous gastrin. The small residual response to 2 DG after antral denervation (Fig.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…3) could be caused by vagal release of gastrin from portions of the stomach or duodenum (14) not included in the antral The findings of the present study confirm an earlier study from this laboratory (13) that the maximal response of HPs to exogenous gastrin was higher than to endogenous gastrin. The small residual response to 2 DG after antral denervation (Fig.…”
supporting
confidence: 86%
“…2 ) or to histamine (Fig. However earlier studies (13) have shown that antral pouches denervated in this way can still release enough gastrin to produce the same maximal response from gastric fistulas as exogenous gastrin. Therefore it is reasonable to conclude that the reductions found in the response of the HP to bathing the mucosa of the antral pouch with acetylcholine or glycine after antral denervation are attributable to changes in the release of gastrin resulting from the surgical procedure for denervation of the antral pouch.…”
mentioning
confidence: 82%
“…Thereby the release of gastrin is dependent upon the quantity and quality of ingested protein (Rérat et al, 1985 ). Gastrin in turn stimulates the pepsinogen secretion from chief cells by activating the appropriate receptors (Cooke et al, 1967 ; Blandizzi et al, 1999 ) and it also induces the secretion of hydrochloric acid by activation of parietal cells either directly or indirectly via histamine released from enterochromaffin-like cells (Sandvik et al, 1987 ). In order to match the gastric activities with the amount of dietary protein in the stomach, the release of gastrin has to be fine-tuned according to the amount of luminal protein; this view implies a continuous assessment of ingested food in the gastric lumen by the G-cells.…”
Section: Introductionmentioning
confidence: 99%